KEMAMPUAN MENULIS PARAGRAF PADA SISWA SEKOLAH DASAR KELAS V DI DIY - NFN Riani (Balai Bahasa Provinsi Riau, 2015)
This study is a qualitative study on 5th grade of primary students competency to write a paragraph. This study aims to describe how the 5th grade students’ ability in writing paragraphs. Qualitative method and purposive sampling data collection are used in this study. The research data is student narrative paragraph from five primary schools in Daerah Istimewa Yogyakarta. The student paragraph is classified and then analyzed based on the theory and requirement of good paragraphs. The result of analysis shows that students are able to write narrative paragraph by telling his/her life experience, such as independence day. Besides, students are also able to write paragraph by regarding its coherence and cohesion. However, students still have some difficulties in making a good paragraph, for example, (1) capital letter is still used in all paragraph; (3) more than one main idea is used in a paragraph; (4) the use of conjunction is less precise; etc